Pd-M1-M2-Sn medium-entropy intermetallic compound catalyst as well as preparation method and application thereof
By introducing metal components such as Fe, Co or Cu into the Cu-based catalyst, the entropy intermetallic compound catalyst is formed in Pd-M1-M2-Sn, which reduces the activity and poor stability of the Cu-based catalyst during the hydrogenation of CO2 to methanol. The problem of this paper significantly improves the selectivity and yield of methanol and enhances the stability of the catalyst.
Patent Information
- Application Number
- CN202411384092.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing Cu-based catalysts have problems such as reduced activity, poor stability and by-product generation in the process of hydrogenation of CO2, which affect the purity and selectivity of methanol.
Using the entropy intermetallic compound catalyst in Pd-M1-M2-Sn, the electronic structure and geometric structure of Pd are regulated by introducing metal components such as Fe, Co or Cu, and an active site is formed that is conducive to CO2 adsorption and methanol desorption. Improve catalytic performance.
It significantly improves the selectivity and yield of methanol, enhances the stability of the catalyst, reduces the adsorption energy of H2O, avoids sintering of active sites, and improves the overall performance of the catalyst.
Smart Images

Figure CN119281348A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a Pd-M1-M2-Sn medium-entropy intermetallic compound catalyst and a preparation method and application thereof. Background Art
[0002] In the process of global response to climate change, reducing greenhouse gas emissions and developing renewable energy have become one of the main tasks. Traditional methanol production usually relies on fossil energy, such as natural gas or coal, which leads to a large amount of CO2 emissions. To this end, electrolyzing water to produce hydrogen through renewable energy (such as solar energy and wind energy), and then hydrogenating hydrogen with CO2 to produce green methanol has become an effective carbon capture and utilization (CCU) technology. This technology can not only achieve carbon recycling, but also replace traditional fossil fuels with high-value-added green methanol, reducing dependence on fossil resources.
[0003] At present, most industrial catalysts for CO2 hydrogenation to methanol use Cu-based catalysts. Although Cu-based catalysts have good performance in CO2 conversion rate and methanol selectivity, they still have certain limitations. For example, the activity of Cu-based catalysts is easily reduced at high temperatures, and the stability of the catalyst is poor during long-term reactions. In addition, Cu-based catalysts are prone to generate by-products, such as carbon monoxide, during the reaction process, which will affect the purity and selectivity of methanol. Therefore, research and development of new, efficient and stable CO2 hydrogenation to methanol catalysts has become an important topic in the current catalyst field.
[0004] In recent years, intermediate-entropy and high-entropy alloy catalysts have attracted widespread attention due to their excellent stability, structural tunability and high catalytic activity. Intermediate-entropy metal compound catalysts have diverse active sites and strong metal-metal interactions, which can effectively improve the activity and selectivity of catalysts. In the process of selective hydrogenation of CO2 to methanol, Pd-based catalysts are considered to be one of the potential high-efficiency catalyst materials due to their high activity in hydrogenation reactions. However, single metal Pd catalysts may have problems such as insufficient structural stability and high price during the reaction. Therefore, it is necessary to introduce other metal components to regulate the electronic structure and geometric structure of Pd-based catalysts in order to improve their catalytic performance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a Pd-M1-M2-Sn medium-entropy metal compound catalyst and a preparation method thereof, utilizing the characteristics of adjustable composition of the main layer plates of layered double hydroxide and easy exchange of interlayer anions, and introducing other metal components to regulate the spatial structure and electronic structure of the Pd active site, so as to form a Pd-M1-M2 tridentate vacancy active site that is beneficial to CO2 adsorption and a Pd-M1-M2-Sn tetradentate rhombus active site that is beneficial to methanol desorption, thereby improving the catalytic performance of the catalyst, and applying the catalyst to the catalytic hydrogenation of carbon dioxide to prepare methanol, thereby improving the yield of methanol.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention is to provide a Pd-M1-M2-Sn mesogenetic intermetallic compound catalyst, wherein the active metal components M1 and M2 are both selected from one of Fe, Co and Cu; and M1 and M2 are different; the four metals in the catalyst together constitute a Pd-M1-M2-Sn multi-dentate rhombus active site, and form a Pd-M1-M2-Sn quadruple site structure composed of electron-deficient M1, M2, Sn and isolated electron-rich Pd.
[0008] The Pd-M1-M2-Sn mesogenetic intermetallic compound catalyst provided by the present invention comprises four metals Pd, M1, M2 and Sn in the catalyst, which together constitute a unique surface active site. By jointly regulating the geometric structure and electron distribution of the active site of the Pd-M1-M2-Sn group, a Pd-M1-M2 tridentate vacancy active site that is beneficial to CO2 adsorption and a Pd-M1-M2-Sn tetradentate rhombus active site that is beneficial to methanol desorption are formed. The localized electron cloud structure of the main active metal Pd is regulated by the low electronegativity guest metals M1, M2 and Sn, forming a surface active site formed by the electron-deficient M1, M2 and Sn and the isolated electron-rich Pd. The Pd-M1-M2-Sn quadruple site structure is formed; the synergistic effect of the active sites of the Pd-M1-M2-Sn groups in the catalyst of the present invention strengthens the adsorption activation of the reactant CO2 on the Pd-M1-M2 tridentate vacancy active site and the adsorption dissociation of H2 on the M1-M2-Sn tridentate vacancy active site, which is beneficial to the subsequent selective hydrogenation reaction; thanks to the regulation of the geometry and electronic properties of the Pd site by the M1, M2, and Sn sites, the adsorption energy of the products methanol and water is reduced, the adsorption of H2O on the active site is weakened, the sintering of the catalyst active site and the occurrence of insufficient stability are avoided, and the CO2 hydrogenation to produce methanol is synergistically catalyzed.
[0009] Furthermore, in the Pd-M1-M2-Sn mesogenetic intermetallic compound catalyst, the molar ratio of metals Pd, M1, M2 and Sn is 1:1:1:1.
[0010] The second aspect of the present invention is to provide a method for preparing the above-mentioned Pd-M1-M2-Sn medium entropy metal compound catalyst, comprising the following steps:
[0011] S1. Nitrates of Mg, Al, M1, and M2 are used as carrier precursors to prepare a first solution, and a Mg / Al / M1 / M2 layered hydroxide solution is prepared by a coprecipitation method. A Pd precursor solution and a Sn precursor solution are sequentially added to the Mg / Al / M1 / M2 layered hydroxide solution for ion exchange and in-situ growth, followed by filtration, washing, and drying to obtain a Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material;
[0012] S2. thermally reducing the Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material to obtain a Pd-M1-M2-Sn medium entropy intermetallic compound catalyst;
[0013] Among them, M1 and M2 are both selected from one of Fe, Co and Cu, and M1 and M2 are different; the molar ratio of Mg and Al ions in the first solution is 3:1; the molar ratio of Pd ions in the Pd precursor solution, Sn ions in the Sn precursor solution, and M1 and M2 ions in the first solution is Pd:Sn:M1:M2=1:1:1:1.
[0014] The preparation method of the Pd-M1-M2-Sn medium-entropy metal compound catalyst of the present invention modifies the Pd-based catalyst based on the main layer plate composition and element adjustable characteristics of the layered double hydroxide material, adopts a coprecipitation method to prepare a Pd / M1 / M2 / Sn / Mg / Al hexalayered double hydroxide, and combines it with a subsequent thermal reduction process to achieve controllable preparation of different Pd-M1-M2-Sn medium-entropy metal compound catalysts; during the thermal reduction treatment process, medium-entropy alloy metal particles Pd-M1-M2-Sn and Mg-Al-O metal oxides are simultaneously generated, so that a strong interaction force is formed between the generated alloy particles and the metal oxide, avoiding the metal particle agglomeration phenomenon caused by high-temperature roasting and high-temperature thermal reduction in the traditional impregnation method, thereby improving the utilization rate of the active components Pd and M1, M2, and further improving the catalytic activity.
[0015] Furthermore, in step S1, the nitrates of Mg, Al, Fe, Co and Cu are respectively magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate and copper nitrate trihydrate; the Pd precursor is selected from one of PdCl2, H2PdCl4, Na2PdCl4 or K2PdCl4; and the Sn precursor is SnCl4·5H2O.
[0016] Furthermore, the Pd precursor is H2PdCl4.
[0017] Furthermore, in step S1, the first solution, the Pd precursor solution and the Sn precursor solution are added to the precipitant in sequence under stirring conditions, and the addition rates of the first solution, the Pd precursor solution and the Sn precursor solution are controlled to be 0.8-1.2 ml / min. During the addition process, the temperature of the reaction system is maintained at 55-75°C, and the pH value of the reaction system is controlled at 10±1 by a pH regulator; after the addition is completed, the reaction is continued to be stirred for 10-20 hours, and finally filtered, washed and dried to obtain a Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material.
[0018] Furthermore, the precipitant is one or more of Na2CO3 solution, NaHCO3 solution or K2CO3 solution, and its CO3 2- The molar concentration is 0.3-0.5 mol / L; the pH regulator is a NaOH solution or a KOH solution, wherein the OH - The molar concentration is 0.8~1.2mol / L.
[0019] Furthermore, the drying condition in step S1 is 100-120° C. and the drying time is 12-20 hours.
[0020] Furthermore, the thermal reduction treatment conditions in step S2 are reduction at 800-1000° C. for 3-5 hours in a H 2 / Ar atmosphere.
[0021] The third aspect of the present invention is to provide an application of the above-mentioned Pd-M1-M2-Sn medium entropy metal compound catalyst in the catalytic hydrogenation of carbon dioxide to produce methanol. The conditions of the carbon dioxide hydrogenation to produce methanol reaction include: a reaction temperature of 200-300°C and a pressure of 3-5MPa; a gas composition of 20-25% carbon dioxide, 60-75% hydrogen, and the balance gas is argon.
[0022] Compared with the use of the existing Pd3Sn catalyst, the methanol selectivity and yield are significantly improved by using the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst of the present invention for catalytic hydrogenation of carbon dioxide to prepare methanol.
[0023] Furthermore, the conditions for the carbon dioxide hydrogenation reaction to produce methanol are: reaction temperature 200-240° C., and pressure 3 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst Z1-900-4 prepared in Example 1.
[0025] Figure 2 This is the XRD spectrum of the Pd-Co-Cu-Sn medium entropy metal compound catalyst Z1-900-4 prepared in Example 1.
[0026] Figure 3 This is a transmission electron microscope image of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst Z1-900-4 prepared in Example 1.
[0027] Figure 4 This is the transmission electron microscope elemental analysis diagram of the Pd-Co-Cu-Sn medium entropy metal compound catalyst Z1-900-4 prepared in Example 1.
[0028] Figure 5 Figure a is a transmission electron microscope image of the Pd-Co-Cu-Sn medium entropy metal compound catalyst Z1-900-4 prepared in Example 1, and Figure b is the corresponding transmission electron microscope XPS line scan elemental analysis image.
[0029] Figure 6 Figure a is a spherical aberration electron microscope image of the Pd-Co-Cu-Sn medium entropy metal compound catalyst Z1-900-4 prepared in Example 1, Figure b is a Fourier image of the catalyst, Figure c is an intensity distribution diagram of the atomic image along the arrow in Figure a, and Figure d is an enlarged view of the matrix marked area in Figure a and the corresponding Crystal model with zone axis projection.
[0030] Figure 7 This is the two-dimensional differential charge diagram of the Pd-Co-Cu-Sn medium entropy metal compound catalyst Z1-900-4 prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention is described in detail and completely with specific embodiments and in conjunction with the accompanying drawings. It should be understood that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0032] Example 1
[0033] The preparation of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0034] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0035] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution.
[0036] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0037] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0038] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0039] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 65°C for 16 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 110°C for 16 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Cu / Sn / Mg / Al hexa-layered hydroxide material;
[0040] S2. Reduce the Pd / Co / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 900°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 4 hours to obtain a Pd-Co-Cu-Sn intermetallic compound catalyst, which is labeled as Z1-900-4.
[0041] The catalyst prepared in this example is characterized as follows: The XRD spectrum of the Pd-Co-Cu-Sn medium entropy alloy intermetallic compound catalyst Z1-900-4 prepared in this example is as follows: Figure 2 As shown, the results show that the medium-entropy intermetallic compound synthesized by the present invention has a distinct crystal structure, and the diffraction intensity of the (111) crystal plane is the highest, indicating that this crystal plane accounts for the largest proportion in the surface distribution of the medium-entropy alloy particles. Figure 3The transmission electron microscope image of the Pd-Co-Cu-Sn catalyst Z1-900-4 prepared in this example shows that the synthesized medium-entropy intermetallic compound catalyst has clear lattice fringes, which also verifies Figure 2 The XRD results in Figure 4 prove that the catalyst has an obvious crystalline structure. Figure 4 The local element analysis of the Pd-Co-Cu-Sn catalyst Z1-900-4 prepared in this example shows that the Pd, Co, Cu, and Sn elements are evenly distributed, indicating that a Pd-Co-Cu-Sn medium entropy alloy crystal phase has been formed. Figure 5 Figure a is a transmission electron microscope image of the Pd-Co-Cu-Sn catalyst Z1-900-4 prepared in this example, and Figure b is a corresponding transmission electron microscope XPS line scan element analysis image. The results show that the Pd, Co, Cu, and Sn elements are evenly distributed, which is consistent with the Figure 4 The analysis results are consistent with those in .
[0042] The catalyst prepared in this example was further characterized by spherical aberration electron microscopy. Figure 6 As shown. In Figure a, the lattice spacing along the arrow direction is 0.234nm, corresponding to the (111) crystal plane of the medium-entropy alloy Pd-Co-Cu-Sn. It should be noted that since the atomic radii of the elements Pd, Co, and Cu are relatively close, the lattice spacing does not change significantly when the guest metals Co and Cu replace the Pd sites in the parent metal Pd3Sn. Figure 6 Figure d in the figure further shows the atomic arrangement of the catalyst particles, indicating that it is highly consistent with the density functional theory calculation simulation results of Pd-Co-Cu-Sn, and the four metal element sites are arranged in an orderly manner, forming a four-fold site structure of Pd-Co-Cu-Sn. According to the corresponding XPS line scan analysis diagram, it can be observed that the Pd, Co, Cu, and Sn elements in the Pd-Co-Cu-Sn intermetallic compound catalyst are evenly distributed, and the content ratio of each element is close to 1:1:1:1.
[0043] The charge analysis of Pd-Co-Cu-Sn catalyst Z1-900-4 was performed, and the results were as follows: Figure 7 The charge is mainly distributed at the Pd site, indicating that the guest metals M1, M2, and Sn transfer electrons to the main active metal Pd, forming a Pd-Co-Cu-Sn quadruple site structure consisting of electron-deficient M1, M2, Sn and isolated electron-rich Pd.
[0044] Example 2
[0045] The preparation of the Pd-Co-Fe-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0046] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.1136 g Fe(NO3)3·9H2O were dissolved in 50 mL ultrapure water and subjected to ultrasonic dispersion treatment to obtain a first solution for standby use;
[0047] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution;
[0048] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0049] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0050] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0051] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 65°C for 16 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 110°C for 16 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Fe / Sn / Mg / Al hexa-layered hydroxide material;
[0052] S2. Reduce the Pd / Co / Fe / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 900°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 4 hours to obtain a Pd-Co-Fe-Sn intermetallic compound catalyst, which is labeled as Z2-900-4.
[0053] Example 3
[0054] The preparation of the Pd-Fe-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0055] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.1136 g Fe(NO3)2·9H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0056] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution;
[0057] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0058] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0059] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0060] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 65°C for 16 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 110°C for 16 hours, followed by sufficient mechanical grinding to obtain a Pd / Fe / Cu / Sn / Mg / Al hexa-layered hydroxide material;
[0061] S2. Reduce the Pd / Fe / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 900°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 4 hours to obtain a Pd-Fe-Cu-Sn intermetallic compound catalyst, which is labeled as Z3-900-4.
[0062] Example 4
[0063] The preparation of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0064] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0065] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution.
[0066] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0067] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0068] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0069] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 65°C for 16 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 110°C for 16 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Cu / Sn / Mg / Al hexa-layered hydroxide material;
[0070] S2. Reduce the Pd / Co / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 900°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 3 hours to obtain a Pd-Co-Cu-Sn intermetallic compound catalyst, which is labeled as Z4-900-3.
[0071] Example 5
[0072] The preparation of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0073] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0074] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution.
[0075] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0076] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0077] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0078] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 65°C for 16 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 110°C for 16 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Cu / Sn / Mg / Al hexa-layered hydroxide material;
[0079] S2. Reduce the Pd / Co / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 900°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 5 hours to obtain a Pd-Co-Cu-Sn intermetallic compound catalyst, which is labeled as Z5-900-5.
[0080] Example 6
[0081] The preparation of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0082] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0083] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution.
[0084] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0085] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0086] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0087] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 55°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 55°C for 20 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block cake, which was dried at 100°C for 20 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Cu / Sn / Mg / Al hexa-element layered hydroxide material;
[0088] S2. Reduce the Pd / Co / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 800°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 5 hours to obtain a Pd-Co-Cu-Sn intermetallic compound catalyst, which is labeled as Z6-800-5.
[0089] Example 7
[0090] The preparation of the Pd-Co-Cu-Sn medium entropy intermetallic compound catalyst of this embodiment comprises the following steps:
[0091] S1. 7.69 g Mg(NO3)2·6H2O, 3.75 g Al(NO3)3·9H2O, 0.0818 g Co(NO3)2·6H2O and 0.0679 g Cu(NO3)2·3H2O were dissolved in 50 mL ultrapure water and dispersed by ultrasonic to obtain a first solution for standby use;
[0092] 0.0919 g H2PdCl4 was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a chloropalladic acid solution, which was used as a Pd precursor solution.
[0093] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water, and after ultrasonic dispersion, a tin tetrachloride solution was obtained, which was used as a Sn precursor solution;
[0094] Dissolve 2.12 g of Na2CO3 powder in 50 mL of ultrapure water and disperse by ultrasonic to obtain a sodium carbonate solution, which is used as a precipitant;
[0095] Dissolve 6.00 g of NaOH powder in 150 mL of ultrapure water and, after ultrasonic dispersion, obtain a sodium hydroxide solution, which is used as a pH adjuster;
[0096] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 75°C for 1 hour. Then, at a rotation speed of 120 r / min, the first solution, Pd precursor solution and Sn precursor solution were added dropwise to the three-necked flask in turn, and the addition rate of the first solution, Pd precursor solution and Sn precursor solution was controlled by a constant flow pump to be 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to ensure that the pH value of the reaction system was stable at 10.5. After the addition was completed, the reaction was continued to be vigorously stirred at 75°C for 12 hours, followed by vacuum filtration, and washed with pure water while filtration until the washing liquid was neutral to obtain a straw yellow block filter cake, which was dried at 120°C for 12 hours, followed by sufficient mechanical grinding to obtain a Pd / Co / Cu / Sn / Mg / Al hexa-element layered hydroxide material;
[0097] S2. Reduce the Pd / Co / Cu / Sn / Mg / Al hexalayered hydroxide material prepared in step S1 at 1000°C in an atmosphere of H2 / Ar (volume ratio 1:4) for 3 hours to obtain a Pd-Co-Cu-Sn intermetallic compound catalyst, which is labeled as Z7-1000-3.
[0098] Figure 1 This is a schematic diagram of the structure of the medium-entropy intermetallic compound catalysts Z1-900-4, Z4-900-3, Z5-900-5, Z6-800-5, and Z7-1000-3 prepared in Example 1 and Examples 4 to 7. It can be seen that the design idea of the medium-entropy intermetallic compound catalyst is to replace the two Pd sites in the Pd3Sn parent metal with active components M1 and M2.
[0099] Comparative Example 1
[0100] The preparation of the Pd3Sn intermetallic compound catalyst of this comparative example comprises the following steps:
[0101] (1) 7.69 g of Mg(NO3)2·6H2O and 3.75 g of Al(NO3)3·9H2O were dissolved in 50 mL of ultrapure water, and then dispersed by ultrasonic to obtain a magnesium aluminum nitrate solution;
[0102] Dissolve 0.2756 g H2PdCl4 in 25 mL ultrapure water and obtain chloropalladic acid solution after ultrasonic dispersion;
[0103] 0.0984 g SnCl4·5H2O was dissolved in 25 mL ultrapure water and dispersed by ultrasonic to obtain a tin tetrachloride solution;
[0104] 2.12 g of Na2CO3 powder was dissolved in 50 mL of ultrapure water and dispersed by ultrasonic to prepare a precipitant;
[0105] 6.00 g of NaOH powder was dissolved in 150 mL of ultrapure water and then dispersed by ultrasonic to prepare a pH regulator;
[0106] The precipitant was transferred to a 500 mL three-necked flask and treated at a constant temperature in an oil bath at 65°C for 1 hour. Subsequently, the magnesium aluminum nitrate solution, the chloropalladic acid solution and the tin tetrachloride solution were added dropwise to the three-necked flask at a speed of 120 r / min, and the feeding rate was controlled to be 1.0 mL / min using a constant flow pump; at the same time, a pH regulator was added through a constant flow pump to keep the pH value of the reaction system constant at 10.5. After the addition was completed, the mixture was stirred vigorously at 65°C for 16 hours, followed by vacuum filtration and multiple washings until the pH was neutral, and finally a brown block solid was obtained.
[0107] (2) The brown block solid obtained in step (1) is dried at 110° C. for 16 hours, and then fully mechanically ground to obtain a Pd / Sn / Mg / Al quaternary layered hydroxide material.
[0108] (3) The quaternary layered hydroxide material prepared in step (2) was reduced at 900° C. in an atmosphere of H 2 / Ar (volume ratio 1:4) for 4 hours to obtain a Pd 3 Sn intermetallic compound catalyst, which was labeled as Z8-900-4.
[0109] Evaluation of Catalyst Performance for Carbon Dioxide Hydrogenation
[0110] The activity of the selective hydrogenation reaction of carbon dioxide was evaluated using the Pd-M1-M2-Sn medium entropy intermetallic compound catalysts prepared in Examples 1 to 7 and the Pd3Sn catalyst prepared in Comparative Example 1. The performance evaluation of the carbon dioxide hydrogenation reaction was carried out on the ZKJC-RJ-X system of Beijing Wanlonghe Technology Co., Ltd., where:
[0111] The components of reactants and products were analyzed online using a 3-channel chromatograph GC9790Plus (Fuli Company, China).
[0112] The chromatographic system is equipped with three detectors: the first is a thermal conductivity detector (TCD) with GDX-01 and GDX-02 columns for detecting non-condensable gases such as H2, CO, CH4, CO2, etc. The second is a flame ionization detector (FID) with RB-INNOWAX columns for analyzing hydrocarbons. The concentration of each component in the product can be accurately determined by the comprehensive external standard method.
[0113] The evaluation conditions are as follows: total inlet flow rate of 60 mL / min, raw gas composition of 24% CO2, 72% H2 and 4% Ar, reaction temperature range of 200-300°C, pressure of 3-5 MPa, and catalyst loading of 150 mg.
[0114] Weigh 150 mg of catalyst sample, mix it evenly with 350 mg of quartz sand, and then load it into the constant temperature zone of the stainless steel reaction tube. After the catalyst is loaded, first check the reaction system for leaks, and introduce a certain pressure of argon (such as 10 bar) into the system. If the pressure remains unchanged, it means that the reaction system is well sealed, and then the evaluation experiment can be carried out.
[0115] Set the nitrogen flow rate to 20sccm (Standard Cubic Centimeter Per Minute), raise the temperature to the reduction temperature; then turn off the argon gas, set the hydrogen flow rate to 20sccm, and turn off the hydrogen after a certain period of reduction; then set the argon flow rate to 20sccm, cool down to the reaction temperature, and set the pressure required for the reaction. After the reaction conditions are stable, set the flow rate of each reaction component, and switch the furnace six-way valve to bypass so that the mixed gas directly enters the chromatogram to detect the concentration of each component before the reaction. After stabilization, switch the furnace six-way valve back, the mixed gas enters the reaction tube to start the reaction, and the gas at the outlet of the reaction tube enters the online chromatogram for detection.
[0116] The catalytic performance of the catalyst in the CO2 selective hydrogenation to methanol reaction was evaluated by testing the CO2 conversion rate, methanol selectivity and methanol yield of the Pd3Sn catalyst prepared in Comparative Example 1 and the Pd-M1-M2-Sn medium entropy metal compound catalyst prepared in Examples 1 to 7, wherein:
[0117]
[0118] Y(CH3OH)=C(CO2)×S(CH3OH)×100%
[0119] The catalytic performance evaluation results of the catalysts prepared in the embodiments and comparative examples are shown in Tables 1 to 3 below:
[0120] Table 1. Catalyst carbon dioxide hydrogenation conversion rate (%)
[0121]
[0122] Table 2. Catalyst CO2 hydrogenation methanol selectivity (%)
[0123]
[0124] Table 3. Catalyst carbon dioxide hydrogenation methanol yield
[0125]
[0126] Combined with the results shown in Tables 1 to 3, it can be seen that the Pd-M1-M2-Sn medium entropy metal compound catalyst of the present invention has significantly improved methanol selectivity and yield compared with the Pd3Sn catalyst. In the range of 200-240°C, the Pd-M1-M2-Sn medium entropy metal compound catalysts prepared in the examples all showed extremely high methanol selectivity, especially the Pd-Co-Cu-Sn catalyst prepared in Example 1 had better carbon dioxide conversion rate and methanol selectivity. This shows that the Pd-M1-M2-Sn medium entropy metal compound catalyst prepared by the technical solution of the present invention can significantly improve carbon dioxide conversion rate, methanol selectivity and yield compared with the Pd3Sn catalyst.
[0127] Evaluation of Catalyst Stability for Carbon Dioxide Hydrogenation
[0128] The Z1-900-4 catalyst prepared in Example 1 was then selected, and the stability of the catalyst was evaluated at 220° C. according to the catalyst performance test method of the above-mentioned carbon dioxide hydrogenation performance evaluation experiment. The test results of CO2 conversion rate C(CO2), selectivity S(CH3OH) and methanol yield Y(CH3OH) are shown in Table 4.
[0129] Table 4. Evaluation of stability of Z1-900-4 catalyst for carbon dioxide hydrogenation
[0130]
[0131] From the results shown in Table 4, it can be seen that after 48 hours of reaction, the carbon dioxide conversion rate of the Z1-900-4 catalyst prepared in Example 1 remains at the same level, and the methanol selectivity is still as high as 99%, which shows that the catalyst has good stability.
[0132] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable professionals familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A Pd-M1-M2-Sn medium entropy intermetallic compound catalyst, characterized in that: The active metal components M1 and M2 are both selected from one of Fe, Co and Cu; and M1 and M2 are different; the four metals in the catalyst together constitute a Pd-M1-M2-Sn multi-dentate rhombus active site, and form a Pd-M1-M2-Sn quadruple site structure composed of electron-deficient M1, M2, Sn and isolated electron-rich Pd.
2. A method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 1, characterized in that: The following steps are involved: S1. Nitrates of Mg, Al, M1, and M2 are used as carrier precursors to prepare a first solution, and a Mg / Al / M1 / M2 layered hydroxide solution is prepared by a coprecipitation method. A Pd precursor solution and a Sn precursor solution are sequentially added to the Mg / Al / M1 / M2 layered hydroxide solution for ion exchange and in-situ growth, followed by filtration, washing, and drying to obtain a Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material; S2. thermally reducing the Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material to obtain a Pd-M1-M2-Sn medium entropy intermetallic compound catalyst; Among them, M1 and M2 are both selected from one of Fe, Co and Cu, and M1 and M2 are different; the molar ratio of Mg and Al ions in the first solution is 3:1; the molar ratio of Pd ions in the Pd precursor solution, Sn ions in the Sn precursor solution, and M1 and M2 ions in the first solution is Pd:Sn:M1:M2=1:1:1:
1.
3. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 2, characterized in that: In the step S1, the nitrates of Mg, Al, Fe, Co and Cu are respectively magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate and copper nitrate trihydrate; the Pd precursor is selected from one of PdCl2, H2PdCl4, Na2PdCl4 or K2PdCl4; and the Sn precursor is SnCl4·5H2O.
4. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 2, characterized in that: The Pd precursor is H2PdCl4.
5. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 2, characterized in that: In the step S1, the first solution, the Pd precursor solution and the Sn precursor solution are sequentially added to the precipitant under stirring conditions, the addition rates of the first solution, the Pd precursor solution and the Sn precursor solution are controlled to be 0.8-1.2 mL / min, the temperature of the reaction system is maintained at 55-75° C. during the addition process, and the pH value of the reaction system is controlled at 10±1 by a pH regulator; after the addition is completed, the stirring reaction is continued for 10-20 hours, and finally, the Pd / M1 / M2 / Sn / Mg / Al hexalayered hydroxide material is obtained by filtering, washing and drying.
6. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 5, characterized in that: The precipitant is one or more of Na2CO3 solution, NaHCO3 solution or K2CO3 solution, and its CO3 2- The molar concentration is 0.3-0.5 mol / L; the pH regulator is a NaOH solution or a KOH solution, wherein the OH - The molar concentration is 0.8~1.2mol / L.
7. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 2, characterized in that: The drying condition in step S1 is 100-120° C. and the drying time is 12-20 hours.
8. The method for preparing the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 2, characterized in that: The thermal reduction treatment conditions in step S2 are reduction at 800-1000° C. for 3-5 hours in a H 2 / Ar atmosphere.
9. Use of the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst according to claim 1 or the Pd-M1-M2-Sn medium entropy intermetallic compound catalyst prepared according to any one of the preparation methods of claims 2 to 8 in the catalytic hydrogenation of carbon dioxide to methanol reaction, wherein the conditions of the carbon dioxide hydrogenation to methanol reaction include: The reaction temperature is 200-300° C., the pressure is 3-5 MPa; the gas composition is: 20-25% carbon dioxide, 60-75% hydrogen, and the balance gas is argon.
10. The use according to claim 9, wherein the conditions for the carbon dioxide hydrogenation to methanol reaction are: reaction temperature 200-240°C, pressure 3MPa.
Citation Information
Cited By
M1-Co3Sn2 monatomic intermetallic compound catalyst for alkene preparation reaction through alkyne selective hydrogenation and preparation method of M1-Co3Sn2 monatomic intermetallic compound catalyst
CN121042059A
M1-co3sn2 monatomic intermetallic compound catalyst for selective hydrogenation of alkyne to olefin and preparation method thereof
CN121042059B
Pd-M1-M2-N-Sn high-entropy intermetallic compound catalyst as well as preparation method and application thereof
CN122517050A